A Technique for Producing Ideas - Young, James Webb, 1886-1973
This is THE classic on creative thinking, written with the clarity, knowledge, and experience of a skilled advertising man. A Technique For Producing Ideas is a step-by-step technique for sparking creativity in advertising or ANY other field...